The Legal Certainty regarding Song Plagiarism Standard in the Indonesian Copyright Law - Suny, Aisha Chandra (Technium Social Sciences Journal, 2022)
Creating a high-quality song requires the author's creativity and hard work. That is the Indonesian Copyright Law protects the author’s right to gain economic benefit and a good reputation for their work. However, many authors are plagiarizing an original piece of work to create an intricate piece of song so that the benefits entail could be obtained more quickly. When a song plagiarism occurs, it is questionable whether the provisions from the Indonesian Copyright Law could provide legal certainty to authors. The theory of legal certainty by Gustav Radbruch will be used to analyze the existing provisions concerning song plagiarism standard and to determine the urgency of creating a song plagiarism standard.